AODTH-002 Full thickness endoscopic colonic resection?– data from the uk ftrd registry. (17th June 2017) - Silva, A Castro; Boger, P; Rahman, I; Bhandari, P; Green, S; Martin, J; Pugh, S; Suzuki, N; Ishaq, S; Patel, P
Abstract : Introduction: Attempts to endoscopically resect non-lifting adenomas, subepithelial tumours, and T1 cancers are very challenging and are traditionally in the realm of surgery. Here we report the first multi-centre UK experience of colonic resections of these lesions using a novel endoscopic full thickness resection device (FTRD) Method: Data on consecutive patients who underwent endoscopic full thickness resection (eFTR) at 6 UK institutions from April 2015 – February 2017 were prospectively analysed. The procedure was undertaken using the, over-the-scope FTRD. Main outcome measures were technical success, total procedure times, histological confirmation of full thickness, R0 resection, technical failures and adverse events. Results: A total of 29 patients underwent eFTR, of which 14 were non-lifting adenomas, 8 T1 polyps and 7 subepithelial tumours. Procedure was technically successful in 89.7% (26/29) cases. The mean age was 68.7 years (39–93 years), median procedure time 38 min (10–80 mins), and median specimen size of 22 mm (13–30 mm). Histology confirmed full thickness resection in 96.2% (25/26) cases, with an R0 resection in 73.1% (19/26) cases. The institution with the greatest number of FTRD cases had a R0 resection of 81.3% (13/16). Technical difficulties occurred in 38.5% (10/26) cases; 5 due to snare failure (R0 still achieved in 4/5 by use of further snare after deployment of device clip), 2 lesions could not be introduced into the FTRD cap, 2 lesions slipped from forceps during clip deployment, and 1 lesion could not be reached with FRTD device, due to sigmoid diverticular segment. There were no cases of immediate or delayed bleeding or perforation. Conclusion: eFTR using the FTRD system is a promising technique allowing full thickness resection of difficult polyps that would otherwise require surgery. Our data demonstrates that it is a safe and effective technique requiring a short but significant learning curve before outcomes similar to European case series are achieved. Reference: . Arthur Schmidt, et al. Endoscopic full-thickness resection in the colorectum with a novel over-the-scope device: first experience. Endoscopy2015; 47(08): 719–725 Disclosure of Interest: None Declared